Shipborne oceanic high-spectral-resolution lidar for accurate estimation of seawater depth-resolved optical properties - Yudi Zhou; Yang Chen; Hongkai Zhao; Cédric Jamet; Davide Dionisi; Malik Chami; Paolo Di Girolamo; James H. Churnside; Aleksey Malinka; Huade Zhao; Dajun Qiu; Tingwei Cui; et al. (Light: Science & Applications, 2022)
Shipborne oceanic high-spectral-resolution lidar for accurate estimation of seawater depth-resolved optical properties